Nutrition in clinical practice - Katz, David L., 1963- (Wolters Kluwer, 2022)
"Introduction Carbohydrate represents the predominant form of all plant matter and is thus a principal dietary source of energy for humans in nearly every culture. Food plants are composed principally of sugars, starches - the carbohydrate energy reserve in plants, cellulose, and other components. Generally, between 40% and 70% of calories are derived from carbohydrate among human populations, with higher amounts prevailing in less developed countries. In contrast, Artic peoples derive most of their food from animals and eat little carbohydrate"--